Can the dispersion methods affect the in vitro ruminal evaluation of substrates with different fermentabilities? - Sampaio, Franciele Caetano (2020)
Ruminant animals are among the main methane (CH4) emitters. As such, efforts have been made to develop feeding strategies for ruminants that mitigate CH4 production. The in vitro incubation is one of the ways to evaluate enteric greenhouse gas production (CH4 and carbon dioxide, CO2), which simulates in the laboratory the fermentation process that occurs in the rumen environment. During the ruminal in vitro fermentation, sample is directly dispersed in the medium, however it has become common to use the F57 filter bags (Ankom®) to quantify the indigestible fraction. Nevertheless, due to its high cost, alternatives such as non-woven textile (NWT – 100 g/m2 ) have been sought, however has not been evaluated in an in vitro gas production system. Thus, our objective was to evaluate the in vitro fermentation products and enteric greenhouse emissions (CH4 and CO2) of substrates with differents forage:concentrate ratios when incubated with N2 headspace within NWT or F57 bags compared to directly dispersion in the medium (DIS). The experiment was conducted according to a 3 × 3 factorial design with 3 delivery methods (samples incubated directly dispersed in the medium, within F57 bags, or within NWT bags) and 3 types of substrates with different forage:concentrate (F:C) ratios (100:0, low-quality tropical grass hay only; 50:50, an equal proportion of concentrate mixture and low-quality tropical grass hay; and 0:100, concentrate mixture only). Rumen fluid was collected of 2 cannulated Holstein steers. The in vitro batch fermentation was carried out using a commercial wireless gas production (GP) apparatus (AnkomRF GP System, Ankom Technology®) during 48h of incubation. There were substrate × delivery methods interactions (P < 0.01) on GP at 24h (GP24) GP at 48h (GP48), in vitro dry matter (IVDMD) and organic matter digestibilities (IVOMD), while no interaction effect was observed on pH (P > 0.05). The GP48, IVDMD, and IVOMD presented similar results on different types of substrates. The GP48 and in vitro digestibilities of the 0:100 F:C ratio substrate were highest in DIS, intermediate in NWT and smallest in F57 (P < 0.05). With 50:50 F:C ratio substrate incubation, there were no differences on GP48 and in vitro digestibilities between DIS and NWT (P > 0.05), but they were greater than F57. The GP48 and digestibilities in NWT were greater than DIS and F57 (P < 0.05) when 100:0 F:C ratio substrates were incubated. The pH was affected by substrate (P < 0.001), where the increasing concentrate inclusion linearly decreased pH from 7.52 to 7.00 (P < 0.001). In 24h of incubation, there was no interaction (P > 0.05) between substrates and delivery method for CH4 and CO2 production (mL/L) and proportion (mL/g DMi and mL/g MOd). The CH4 and CO2 proportion and production relative to DMi presented linearly increase when F:C ratio increased (P < 0.01). On the other hand, with the increase in F:C ratio incubated, there was a linear (P = 0.017) decrease in CH4 and CO2 production relative to MOd. In 48h of incubation, there were interactions between substrates and delivery method (P < 0.01) on CH4 and CO2 production relative to DM incubated (mL/g DMi), but no on production relative to OM digested (mL/g OMd; P > 0.05). The CH4 and CO2 proportions was greater when 0:100 F:C substrate was dispersed in the medium than incubated within F57 and NWT bags, which did not differ between them. The CH4 and CO2 in relation to DM incubated of 0:100 F:C substrate by using DIS was greater than the others methods. For the 50:50 F:C ratio substrate, CH4 at DIS was similar to NWT which was equal to F57, while for 100:0 substrates there was no difference between the methods. There were no differences between methods on CO2 production (mL/g DMi) when 100:0 substrates were incubated, but for 0:100 ratio substrate, CO2 at DIS was greater than the incubation within bags. The CH4 production relative to OM digested at 48h of incubation linearly reduction in response to increase of F:C ratio (P < 0.001). There were no interactions between method × substrate (P > 0.26) on molar proportions of individuals VFA (i.e. acetic, propionic, and butyric), acetic/propionic ratio, and total VFA. The different delivery methods affect molar proportion of propionic acid and acetic/propionic ratio (P < 0.04). The propionic acid (mol/100 mol) presented higher values when substrates were incubated into bags than dispersed in the medium (P < 0.03), but no differences were found for F57 and NWT (P = 0.92). The substrate type affected (P < 0.01) change of total VFA expressed in relation to OM incubated and digested, but no (P > 0.62) for CH4 and CO2 in relation to ΔVFA. Decreasing the proportion of F:C ratio in the substrate generally increased ΔVFA/OMi, while decreased ΔVFA/OMd. In addition, substrate delivery method affected CH4/ΔVFA and CO2/ΔVFA (P < 0.04). The dispersion method presented similar CH4/ΔVFA to NWT (P = 0.39) which was equal to F57 (P = 0.08). However, regarding CO2/ΔVFA, incubation into bags showed lower relative emission (P < 0.001) than when dispersed in the medium (0.31 vs 0.71), while F57 and NWT were not different (P = 0.23).As conclusion, the greenhouse gases emission, digestibility, acetic to propionic ratio are lower when substrates are incubated within filter bags compared with when they are directly dispersed in the medium. However, variables evaluated in F57 and NWT filter bags presented strongly correlated results with the dispersion method, although F57 present some better advantages than NWT bags, but more studies are needed to compare and validate the methods evaluated against in vivo data.